A case for the provision of assisted dying in prisons founded on the right to self-determination: Creating equivalence between prisoners and non-prisoners?. (September 2022) - Fenwick, Daniel; Tomczak, Philippa; Cochrane, Alasdair
This article makes the case for the provision of access to assisted death in prisons, founded on the right to self-determination under Article 8(1) ECHR, in order to create equivalence between prisoners and non-prisoners. It considers possible State justifications for interferences with the right under Article 8(2) and whether they would meet the Convention standards of legality and proportionality. In relation to proportionality, it is argued that the foundational basis for restrictions on assisted dying imposed on both the general and prison populations derives from the concept of human dignity, a concept which is also fundamental to prisoners' rights. Under the banner of proportionality, from an initial presumption of equivalence of access to assisted dying, the article identifies certain conditions inherent in the prison situation that inevitably oppose human dignity and which provide a plausible basis for divergence. Ultimately, it is concluded that an absolute bar on provision of access to assisted dying in prisons cannot be justified, but that the factors that undermine dignity in prison could justify a degree of divergence from creation of equivalence between the prison and the non-prison populations in terms of such access.